ENHANCING STUDENTS' VOCABULARY THROUGH WEB GAMES-BASED LEARNING IN THE INDONESIAN ELEMENTARY SCHOOL SETTING - Ordelia Novela Setiaji; Dana Yudha Kristiawan; Abd Rahman - - (ELITERATE : Journal of English Linguistics and Literature Studies, 2025)
Teaching English vocabulary in Indonesia often faces challenges, especially because students are required to memorize words without understanding their meanings. Many students struggle due to a lack of vocabulary mastery, which results in less effective learning. To address this issue, this article explores the extent to which technology-based learning through the Educaplay web media can impact English vocabulary teaching for elementary school students. This study also highlights several key aspects of vocabulary improvement, including material selection, the implementation of web-based game learning, learning tasks, and material evaluation. This research uses a qualitative descriptive design to provide an in-depth analysis of the issue. The study adopts an intrinsic case study approach to examine specific contexts where Educaplay is used as a teaching tool. The data is analysed using thematic analysis to identify patterns and themes related to vocabulary learning through technology-based learning. The results are as expected, namely vocabulary improvement through interactive media, increased motivation, engagement, and self-confidence, technical and accessibility challenges, and positive reflection and meaningful learning. he results of this study may provide significant implications for educators and policymakers. By integrating innovative web-based learning platforms such as Educaplay, teaching English vocabulary in elementary schools can become more engaging and effective, helping students to better understand and use English vocabulary in their daily lives Keywords: Vocabulary, Games, Technology, Educaplay